Fragments of Modernity (Routledge Revivals) : Theories of Modernity in the Work of Simmel, Kracauer and Benjamin. - Frisby, David (Routledge revivals., 2013)
Fragments of Modernity, first published in 1985, provides a critical introduction to the work of three of the most original German thinkers of the early twentieth century. In their different ways, all three illuminated the experience of the modern urban life, whether in mid nineteenth-century Paris, Berlin at the turn of the twentieth century or later as the vanguard city of the Weimar Republic. They related the new modes of experiencing the world to the maturation of the money economy (Simmel), the process of rationalization of capital (Kracauer) and the fantasy world of commodity fetishism).